THE MAIN DIRECTIONS OF INNOVATIVE MANAGEMENT AND DEVELOPMENT OF SMALL BUSINESS ENTITIES (Conferencea, 2023)
This article discusses the main directions of innovative management and development of small business entities, the economic mechanism of their activity development and its necessity, and models used in planning modern strategies. Measures aimed at the development of the industrial network, the concepts related to the improvement of the economic efficiency of the enterprises, the development of entrepreneurial activities in the industrial network and the organization of these processes, the factors determining the development of small business and private entrepreneurship are defined entrepreneurship, factors embodying entrepreneurship in the industrial sector and enterprises operating in them.